Self-Efficacy and Entrepreneurial Mindset: Towards Societal Re-Engineering - Racheal, Agbonna Adedayo; Obarinu, Agbonna Rasheed (International Journal of Business, Economics and Management, 2020)
Entrepreneurship is a derivative of entrepreneurial learning which promotes functional unemployment reduction through university education. However, universities in Nigeria have turned to producers of unemployed graduates instead of job creators in the face of high rate of global unemployment. This is due to the non appreciation of entrepreneurship among university undergraduates in Nigeria. Few studies have been conducted on the effect of self-efficacy and entrepreneurial mindset for societal, re-engineering with most scholars concentrating on entrepreneurship and economic growth. This study adopted survey research design. The population comprised of 25,353 four hundred level undergraduates in all Federal Universities in South-West, Nigeria. The sample size of 1,673 was obtained using Krejcie and Morgan formula. Stratified random sampling technique was adopted in selecting the respondents. A validated structured questionnaire with Cronbach’s alpha reliability coefficients for the constructs ranging from 0.73 to 0.95 was employed in the study. The response rate was 76.91%. The study adopted stratified random sampling technique and a structured questionnaire with 6-point Likert scale was used for data collection). Self-efficacy had a significant effect on mindsets towards entrepreneurship (R2 = 0.238, t(1671) =22.843, β = 1.029, p<0.05).The study recommended that, government, academia and the society should focus on measure to promote university undergraduates’ self-efficacy.